Traditionally Cultivated Salt Tolerant Rice Varieties Grown in Khazan Lands of Goa, India and Their Grain Quality Characteristics - S. Krishnan*, Shilpa J. Bhonsle and (Journal of Phytology, 2011)
The khazan lands (saline lands) have the potential for growing traditional rice varieties which are salt tolerant during rainy season without supplemental irrigation. In khazan land the rice varieties grown are limited, but specific traditional rice varieties like Korgut, Khochro and Assgo are grown predominantly. During this study, we have collected 10 traditionally cultivated rice varieties which grown in saline areas. These varieties were with unique morphological characteristics of shape, size and color. The physicochemical characteristics such as physical, chemical and cooking characteristics were studied. Among the varieties, the highest hulling (80%) was noted in varieties Muno, Shiedi and lowest in varieties Bello and Kalo Damgo (73%). The Length/Breadth (L/B) ratio ranged from 2.02-2.86. The lowest chalkiness was recorded in variety Kalo Novan (33.30%) and highest in variety Korgut (87.86%). Among the varieties studied, the amylose content (AC) ranged from 14.6-23.7% in variety Khochro and Kalo Novan respectively. The gel consistency was highest in traditionally cultivated rice variety Damgo (75.3 mm) and lowest in Khochro (34.6 mm). Kernel length after cooking (KLAC) ranged from 2.38-4.78 mm. The highest KLAC was recorded in Bello and minimum in variety Korgut. Kernel elongation ratio (ER) ranged from 1.03-1.66. The present investigation revealed that the traditionally cultivated rice varieties viz. Bello, Korgut, Khochro and Kalo Novan were with good grain quality characteristics. Key words: Grain quality, Khazan lands, Physico-chemical properties, Rice diversity <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Shilpa J. Bhonsle and S. Krishnan. Traditionally Cultivated Salt Tolerant Rice Varieties Grown in Khazan Lands of Goa, India and Their Grain Quality Characteristics. J Phytol 3/2 (2011) 11-17